Maximization of the fundamental frequency of plates and cylinders. (15th November 2016) - Trias, D.; Maimí, P.; Blanco, N.
Abstract: This work deals with the maximization of the fundamental frequency of laminated plates and cylinders by finding the optimal stacking sequence for symmetric and balanced laminates with neglectable bending–twisting and torsion–curvature couplings are considered. Instead of using the angle at each ply the so-called lamination parameters are used as design variables. Results for the plate problem are compared to those using analytical expressions found in the literature. The cylinder problem is solved for a large number of thickness and radius-to-length ratio combinations. Values of the optimal stacking sequence are given considering the angle can take any value between 0 ° and 90 ° or the case when the angle can only take a discrete set of values.